2008
DOI: 10.1128/jvi.01447-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD1 Antigen Presentation by Human Cytomegalovirus

Abstract: The betaherpesvirus human cytomegalovirus (HCMV) encodes several molecules that block antigen presentation by the major histocompatibility complex (MHC) proteins. Humans also possess one other family of antigen-presenting molecules, the CD1 family; however, the effect of HCMV on CD1 expression is unknown. The majority of CD1 molecules are classified on the basis of homology as group 1 CD1 and are present almost exclusively on professional antigen-presenting cells such as dendritic cells, which are a major targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Briefly, monocytes incubated with HCMV-related laboratory wild-type strain NEWT were used as targets (22). In addition, autologous LCL were pulsed with 1 mg/ml overlapping HCMV pp65/IE-1 peptide pools, whereas unpulsed LCL were used as control targets.…”
Section: Assessment Of Cytotoxic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, monocytes incubated with HCMV-related laboratory wild-type strain NEWT were used as targets (22). In addition, autologous LCL were pulsed with 1 mg/ml overlapping HCMV pp65/IE-1 peptide pools, whereas unpulsed LCL were used as control targets.…”
Section: Assessment Of Cytotoxic Activitymentioning
confidence: 99%
“…Following reactivation, HCMV early Ags can be presented by circulating monocytes and their derivatives. This can be simulated by infecting monocyte-derived immature dendritic cells (iDC) using HCMV wild-type strain NEWT (22). The lower epitope density on infected cells compared with peptide-loaded cells is a challenge requiring highly effective T cell recognition.…”
Section: Modifying Il-2r Signaling Enables Superior Protective Cd4-mementioning
confidence: 99%
“…These results may be evidence supporting that immature hCD1d undergoes ubiquitin mediated degradation. Previous report showed that the expression of group 1 CD1 molecules (hCD1a, hCD1b, hCD1c) is down-regulated after HCMV infection (Raftery et al, 2008). Interestingly, these down-regulation of group 1 CD1 molecules is not due to HCMV encoded short glycoproteins (US2, US3, US6, and US11), but the transcriptional inhibition of group 1 CD1 molecules through HCMV IL-10 homologue (Raftery et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…Previous report showed that the expression of group 1 CD1 molecules (hCD1a, hCD1b, hCD1c) is down-regulated after HCMV infection (Raftery et al, 2008). Interestingly, these down-regulation of group 1 CD1 molecules is not due to HCMV encoded short glycoproteins (US2, US3, US6, and US11), but the transcriptional inhibition of group 1 CD1 molecules through HCMV IL-10 homologue (Raftery et al, 2008). However, our results indicated that HCMV US2 interacts with hCD1d through direct protein-protein interaction and leads the proteasomal degradation of hCD1d in an ubiquitin-dependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…Monocytederived, immature DC (iDC) are fully permissive to HCMV replication (3), but infection of these cells is restricted to strains expressing the viral genes UL128 to UL131A (4). Infection of iDC by HCMV and its impact on their maturation and function have been studied by several laboratories (5)(6)(7)(8)(9)(10). There is consensus that T cell costimulatory molecules, such as CD40, CD80, and CD86 and MHC classes I and II, are downregulated on the surfaces of iDC following HCMV infection (2).…”
mentioning
confidence: 99%